Distribution of Sodium and Diffusion Mechanism in Sodium Silicate Liquid - Thi Thanh Ha, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 35 No 3DO - 10.25073/2588-1124/vnumap.4354, 2019)
In this study, molecular dynamic simulation is employed to study the structural properties and diffusion mechanism in sodium silicate (Na 2 O.4SiO 4 ). Structural characteristics are clarified through the pair radial distribution function, distribution of SiO x coordination units and network structure. The simulation results reveal that the structure of Na 2 O.4SiO 4 liquid consists of one Si-O network that is mainly formed by SiO 4 units. The spatial distribution of sodium is non-uniform; sodium tends to be in the non-bridging oxygen-simplexes and in larger-radius simplex. Moreover, the sodium density for non-bridging oxygen region is significantly higher than the one for other regions. The study results also show that Si and O diffuse by bond break-reformation mechanism, while the motion of Na consists of two parallel processes. Firstly, Na atoms hop from one to another O within a disordered network where each bridging oxygen (BO) has one site, while a non-bridging oxygen (NBO) possesses two sites. The average resident time for Na staying near NBO is much longer than that near BO.